Development of dioctadecyldimethylammonium bromide/monoolein liposomes for gene delivery - Silva, João P. N. (2012)
The artificial introduction of nucleic acids (NA) into mammalian cells (transfection) has become, in recent years, a well-established procedure in basic and applied research, which allowed the study of gene function and regulation. The advances in this area have made possible the use of these methods for gene-based medicines, which constitute alternative therapeutic approaches. One of the most prominent methods is lipofection that uses cationic liposome/NA complexes (a.k.a. lipoplexes) for the complexation, transport and release of therapeutic sequences into target cells. Although yielding lower transfection efficiencies compared with viral gene delivery, lipofection vectors are much safer for medical applications because no significant mutational or toxicological risk exist. Dioctadecyldimethylammonium Bromide (DODAB)/Monoolein (MO) liposomes have recently been described as a new promising alternative to common transfection reagents, due to the pioneering application of MO as helper lipid in lipoplex formulations. In this chapter, we will review the effect of MO on the physicochemical properties of DODAB/MO liposomes and pDNA/DODAB/MO lipoplexes. How lipoplex properties may affect the interaction with different extracellular components and their cell uptake and trafficking will be discussed. The importance of lipoplex biocompatibility towards efficient gene therapy will also be approached presenting pDNA/DODAB/MO system as a lipoplex model, supporting the use of MO as new helper lipid in lipofection.